Effects of basketball-specific high-intensity interval training on aerobic performance and physical capacities in youth female basketball players - Aschendorf, P. F.; Zinner, C.; Delextrat, A.; Engelmeyer, E.; Mester, J. (The Physician and Sportsmedicine, 2019)
Objective: The goal of this study was to investigate the effects of a 5-week, basketball-specific high-intensity interval training (HIIT) on aerobic performance in youth female basketball players.